An interdisciplinary nationwide complex intervention for lifespan neurodevelopmental service development: Underpinning principles and realist programme theory - Maciver, Donald; Rutherford, Marion; Johnston, Lorna; Curnow, Eleanor; Boilson, Marie; Murray, Mairéad (Frontiers in Rehabilitation Sciences, 2023)
Background: People seeking support for neurodevelopmental differences often report waiting too long for assessment and diagnosis, as well as receiving inadequate support in educational and health settings. The National Autism Implementation Team (NAIT) developed a new national improvement programme in Scotland, focusing on assessment, diagnosis, educational inclusion, and professional learning. The NAIT programme was conducted within health and education services across the lifespan for a range of neurodevelopmental differences, including autism, developmental coordination disorder, developmental language disorder, and attention deficit hyperactivity disorder. NAIT included a multidisciplinary team, with the involvement of an expert stakeholder group, clinicians, teachers, and people with lived experience. This study explores how the NAIT programme was planned, delivered, and received over three years. Design: We performed a retrospective evaluation. We collected data from review of programme documents, consultation with programme leads and consultation with professional stakeholders. A theory-based analysis was completed, drawing on the Medical Research Council Framework for developing and evaluating complex interventions, and Realist analysis methods. We developed a programme theory of the contexts (C), mechanisms (M), and outcomes (O) influencing the NAIT programme, based on comparison and synthesis of evidence. A key focus was on identifying the factors that contributed to the successful implementation of NAIT activities across different domains, including practitioner, institutional and macro levels. Results: On synthesis of the data, we identified the key principles underlying the NAIT programme, the activities and resources utilised by the NAIT team, 16 aspects of context, 13 mechanisms, and 17 outcome areas. Mechanisms and outcomes were grouped at practitioner level, service level and macro level. The programme theory is pertinent to observed practice changes across all stages of referral, diagnosis and support processes within health and education services for neurodivergent children and adults. Conclusions: This theory-informed evaluation has resulted in a clearer and more replicable programme theory that can be used by others with similar aims. This paper illustrates the value of NAIT, realist and complex interventions methodologies as tools for policymakers, practitioners, and researchers.